ENSURING ACCURACY IN SOCIAL SCIENCE RESEARCH: A REVIEW OF VARIABLE CONCEPTUALISATION AND MEASUREMENT - Vandekan, Ungwa Emmanuel; Nomor, Blessing Iveren (African Journal of Social and Behavioural Sciences, 2025)
Accurate variable conceptualisation and measurement are fundamental to the integrity of social science research. Inconsistent definitions, methodological flaws, and measurement errors can undermine research validity, limiting the generalizability of findings. This paper provides a comprehensive review of variable conceptualisation and measurement, examining their significance, challenges, and best practices. The study explores different types of variables, levels of measurement, and measurement scales while emphasising the role of transparency, accountability, and methodological rigor in ensuring data accuracy. Conceptual and operational definitions are discussed in relation to their impact on measurement reliability and validity. Additionally, the paper highlights theoretical and methodological limitations, such as conceptual ambiguity, cultural and linguistic differences, and measurement biases. To enhance research credibility, best practices – including the use of validated measurement instruments, pilot testing, and data quality control – are recommended. The findings highlight the importance of clear conceptual frameworks and strong measurement methods to enhance the reliability and relevance of social science research.